Stirring : theory and practice - Zlokarnik, Marko, ....- (Weinheim : Wiley-VCH, 2001)
1. Stirring, general 2. Stirrer power 3. Homogenization 4. Gas-liquid contacting 5. Suspension of solids in liquids (S/L system) 6. Dispersion in L/L systems 7. Intensification of heat transfer by stirring 8. Mixing and stirring in pipes
Keywords: Mengen; Mengtechnieken; Procestechnologie